Prevalence and risk factors for Trichomonas foetus infection in cattle in northeastern Costa Rica - Ortuno, Ana (1992)
Two studies (one pilot and one cross-sectional) were conducted in the two main livestock-rearing areas of Costa Rica using an improved method (In-Pouch TF) for the detection of Trichomonas foetus infection in bulls. Herd prevalence rates of 6.7% (6/89) and 15.9% (10/63 ), and bull prevalence rates of 3.9% (6/153 ) and 6.2% ( 14/225 ) were found in the pilot and cross-sectional studies, respectively. Adjusted prevalences in the cross-sectional study were 18.4% and 7.2% for farms and bulls, respectively. Breed (Bos taurus) and age (over 4 years) were the main risk factors identified using random-effects logistic regression. The nature of the disease and the high prevalence indicated that trichomoniasis could have a serious economic impact on cattle production in Costa Rica.